2017
DOI: 10.1093/humrep/dex313
|View full text |Cite
|
Sign up to set email alerts
|

New debate: is it time for infertility weight-loss programmes to be couple-based?

Abstract: With obesity on the rise in the general population, it has also become more prevalent among people of reproductive age. Weight loss has shown benefits in overweight women and men experiencing fertility problems. However, the existing weight-loss interventions for individuals with infertility are associated with high drop-out rates and limited success. In this article, we argue for the development of weight-loss programmes targeting couples, as couples are routinely seen in fertility clinics, rather than indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Third, although purposely designed to include both individuals and couples with obesity in the lifestyle intervention programme, possible effects of this difference among participants were not apparent and were included in the statistical model as a random effect factor. Further research is needed, as also previously suggested by other researchers 43 . Fourth, the study was conducted during a period of COVID‐19 lockdown in Denmark.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Third, although purposely designed to include both individuals and couples with obesity in the lifestyle intervention programme, possible effects of this difference among participants were not apparent and were included in the statistical model as a random effect factor. Further research is needed, as also previously suggested by other researchers 43 . Fourth, the study was conducted during a period of COVID‐19 lockdown in Denmark.…”
Section: Discussionmentioning
confidence: 89%
“…Further research is needed, as also previously suggested by other researchers. 43 Fourth, the study was conducted during a period of COVID-19 lockdown in Denmark. This may have influenced weight loss.…”
Section: Limitationsmentioning
confidence: 99%
“…The fact that both interviewed men and women were interested in sexual advice and exercises and wanted both partners to be involved is relevant. Partner participation increased the effectiveness of a sexual advice programme for female sexual dysfunction ( Hurlbert et al , 1993 ) and is expected to increase the adherence of subfertile couples to psychosocial interventions ( Martins et al , 2014 ; Luk and Loke, 2016 ; Best et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Where necessary, this should be acknowledged and studies or interventions aimed at improving fertility in couples actively seeking pregnancy, developed accordingly. In the fertility context, unlike any other, couples attend together for appointments and support each other during treatment 74 . A couple‐based approach to weight loss would be feasible and acceptable in this context.…”
Section: Discussionmentioning
confidence: 99%